2001
DOI: 10.1017/s1752756200004683
|View full text |Cite
|
Sign up to set email alerts
|

Increased intake responses from beef steers zero-grazed on Lolium perenne selected for high levels of water soluble carbohydrate

Abstract: Fresh forages may result in the loss of up to 40% of dietary nitrogen as rumen ammonia, as the microbial population is unable to utilise all the non-protein nitrogen released from rapidly degradable plant proteins. This may be due to the characteristically low levels of readily available energy released in the rumen, primarily as a result of the low levels of water soluble carbohydrate (WSC) in traditional forages. In a previous experiment Lee et al, (1999) found an increase in liveweight gain of pre-weaned la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Water-soluble carbohydrate concentration of pasture grasses is considered an important grazing factor because it increases the amount of readily available carbohydrate, so affecting the efficiency of conversion of nitrogen to microbial protein in the rumen. Miller et al (2001) have reported enhanced milk production and quality in dairy cows and increased live weight gains have been reported in sheep (Lee et al 2000) and in cattle (Lee et al 2001). These studies, however, were based on only two varieties with high and low WSC, which may also have differed in other characteristics in addition to WSC.…”
Section: Nutritive Valuementioning
confidence: 99%
“…Water-soluble carbohydrate concentration of pasture grasses is considered an important grazing factor because it increases the amount of readily available carbohydrate, so affecting the efficiency of conversion of nitrogen to microbial protein in the rumen. Miller et al (2001) have reported enhanced milk production and quality in dairy cows and increased live weight gains have been reported in sheep (Lee et al 2000) and in cattle (Lee et al 2001). These studies, however, were based on only two varieties with high and low WSC, which may also have differed in other characteristics in addition to WSC.…”
Section: Nutritive Valuementioning
confidence: 99%
“…Limited breeding progress in the nutritive value of perennial ryegrass has been achieved in recent decades compared to other crops. One of these breeding advances affecting ruminant nutrition has been the introduction of high-sugar genotypes [8,23,24]. It is therefore very important to identify accession-related differences in the nutritional value of perennial ryegrass.…”
Section: Introductionmentioning
confidence: 99%